Effect of Addition of Organic Ligands on Complexation of Trace Nickel Ions in its Aqueous Solutions onto Chelating-azo-Hydroxyl Functionalized Polystyrene Adsorbents - Alwesabi, Ali Saad; Alabsi, Badr Ismail (Jocpr Publishing, 2019)
In this work, developed, selective, sensitive and reliable method for preconcentration and spectrophotometric determination of trace nickel ions in its aqueous solutions based on formation of mixed-ligand complex in the (complexing absorbent-Ni(II) ions-p-bromo and nitroanilines) system. The effect of addition of p-nitroaniline and p-bromoaniline ligands on complexation of nickel (II) with adsorbents of polystyrene-azo-phenol derivatives from aqueous solutions was investigated. The parameters including optimum acidity (pH opt),the half-adsorption pH value (pH50), time(t) and temperature(T), the adsorption capacity (qm), the stability constant of the complexation (log?) in the presence of a ligand as a third component were extensively investigated under batch (static) conditions. The adsorption selectivity of nickel (II) and the possibility of desorption in this system studied. The structure of the mixed ligand complex was suggested.